Mechanistic and energetic studies of superparamagnetic iron oxide nanoparticles as a cyclophosphamide anticancer drug nanocarrier: A quantum mechanical approach. (February 2019) - Mozayyeni, Neda; Morsali, Ali; Bozorgmehr, Mohammad Reza; Beyramabadi, Safar Ali
Using Fe6 (OH)18 (H2 O)6 as a ring cluster model for superparamagnetic iron oxide nanoparticles, noncovalent configurations and three mechanisms of covalent functionalization of superparamagnetic iron oxide nanoparticles with cyclophosphamide an anticancer drug were studied. Quantum molecular descriptors, solvation, and binding energies of noncovalent interactions were investigated the in gas and solution phases at the B3LYP and M06-2X density functional levels. In the vicinity of superparamagnetic iron oxide nanoparticles, the reactivity of the drug increases, showing cyclophosphamide can probably bind to superparamagnetic iron oxide nanoparticles through Cl ( k 1 mechanism), P=O ( k 2 mechanism), and NH in a six-membered ring ( k 3 mechanism) groups. The activation parameters of all pathways were calculated, indicating the high barriers related to the k 1 and k 2 mechanisms are higher the barrier related to the k 3 mechanism. The k 3 mechanism is also spontaneous and exothermic and is therefore the preferred mechanism for covalent functionalization.